PERTUMBUHAN TANAMAN BAWANG MERAH VARIETAS LEMBAH PALU YANG DIBERIKAN BERBAGAI KONSENTRASI ATONIK - Ahmad Deedad; Sakka Samudin; Muhammad Ansar (Agroland: Jurnal Ilmu-ilmu Pertanian, 2017)
This study aimed to determine the influence of atonic concentrations which can increase plant growth and yield of shallot (Allium cepa L. Aggregatum Group) of Lembah Palu variety.  This study was conducted from February to May 2015in Bulupountu village, Sigi District, Central Sulawesi Province.  This study used a Randomized Block designin which grouping was based on diameter of shallot bulbs. Five treatments with four replicates were applied including Control (A0), 0.25 ml atonic/l water(A1),0.50 ml atonic/l water (A2), 0.75 ml atonic/l water(A3), and 1.0 ml atonic/l water (A4).Datawas analyzed using analysis of variance (ANOVA) followed by a HSD test at 5% if the atonic effect was significant.  The atonic concentrations significantly affected the growth and yield of Lembah Palu shallot variety in which the best treatment was found in the application of 1.0 ml atonic/l water.  Keywords: Atonic, Lembah Palu shallot variety.